TANGGUNG JAWAB NOTARIS ATAS PERBUATAN MELAWAN HUKUM MELAKUKAN PEMALSUAN SURAT KUASA MENJUAL DALAM AKTA JUAL BELI (STUDI KASUS PUTUSAN PENGADILAN NEGERI TANGERANG NOMOR 1443/PID.B/2018/PN.TNG) - Eka Aprilia; R. Rahaditya (Fakultas Hukum Universitas Tarumanagara, 2021)
Counterfeiting can be classified as a crime of fraud. Criminal acts in the form of falsification of the provisions are contained in Article 263 to Article 265 of the Criminal Code. The problem faced is how the notary's responsibility for unlawful acts is to falsify the power of attorney to sell in the deed of sale (Case Study of Tangerang District Court Decision Number 1443/Pid.B/2018/PN.Tng.). The research method used is a normative juridical legal research method. The results of the study indicate that the responsibility of the notary for unlawful acts is to falsify the power of attorney to sell in the deed of sale and purchase related to the Tangerang District Court Decision Number 1443/Pid.B/2018/PN.Tng. is the proof of the actions committed by Notary Dr. Bambang Sudirmanto, SH, MKn intentionally with full awareness in planning fraudulent acts that cause losses, the notary can be subject to administrative sanctions as stipulated in Article 85 of the UUJN regarding violations of Article 16 paragraph (1) letter a of the UUJN. Sanctions that can be imposed are verbal warnings, written warnings, temporary dismissals, respectful and dishonorable dismissals. Can also be subject to criminal sanctions. In order to protect the interests of the notary parties, they must act in accordance with the laws and regulations for the position of a notary and uphold the notary code of ethics.